Agriculture's contribution to the economic recovery: Possibilities of reducing the current input crises - Mihai Berca; Valentina-Ofelia Robescu; Roxana Horoiaş (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
This paper approaches an extremely current topic, namely the substitution of synthetic nitrogen, very expensive and polluting, with nitrogen of biological synthesis, through the peas and Rhizobium system, cheap and nonpolluting. The entire economy is going through a period of crises, generated by people's ineptitude in managing precisely their most important problems, namely those of food and social security and safety. Over time, there has been a correlation between the price of gas, which 80% goes into the nitrogen processing, and that of fertilizers. In 2022, the price of gas increased, on average, 9 times, reaching 450 EUR/1000 m3 , and the price of fertilizers reached 1200 EUR/t. Between 2020 and 2022, the fuel price also doubled, and the value of other inputs was well above the multiplier of 2. By mid-2022, the price of wheat increased from 80-85 EUR/t, to 300-310 EUR/t, with very large fluctuations even from one day to another. However, the high price of wheat cannot cover all the expenses involved in the cultivation process, which puts mankind's bread in danger. The situation is similar for other agricultural crops. It's becoming clear that there is an urgent need to turn over research in order to find solutions for ameliorate the state of deep crisis in which bread and other food production are, as well as public health, after two years of the Covid-19 pandemic and during a war in the immediate vicinity of Romania's borders.
Keywords: Q11; Q12; Q14; Q16; Q17; 330; wheat; peas; inputs; crisis; price increase